Flow backup caused by structures within open channel - Chen, Jiayi. (2009)
With the introduction of the Active, Beautiful, Clean program, hydraulic structures such as piers may be required to be built within water channels to support decks built over the water channels. These hydraulic structures may cause excessive flow backup, resulting in flooding on the upstream. This study is done to study how to minimize the impact caused by these hydraulic structures.